Edukasi Gizi Ibu Hamil dan Pencegahan Stunting dengan Media Flipchart Meningkatkan Pengetahuan - Khoirunisa, Sonia; Astuti, Sri Lestari Dwi; Handayani, Siti (Poltekkes Kemenkes Surakarta, 2023)
Background: The main problem in this community service programme is the low level of knowledge among pregnant women regarding nutrition in efforts to prevent stunting in the Cepogo Community Health Centre working area, particularly in three villages with high stunting rates in Boyolali Regency. The aim of the activity is to increase the nutritional knowledge of pregnant women so that they are able to effectively prevent stunting through education using flipcharts. Methods: The methods used included counseling with flipcharts and leaflets for 31 primigravida pregnant women. Participants were selected using purposive sampling according to inclusion and exclusion criteria. The activity was carried out through door-to-door socialisation, pre-tests and post-tests to measure knowledge before and after education, and evaluation using a Guttman scale questionnaire that had been tested for validity and reliability. Results: The results showed a significant increase in the knowledge of pregnant women; before the activity, 77.4% of participants had poor knowledge, but after education using flipcharts, there was an increase to 77.4% of participants in the good category based on the post-test results. The p-value in the Wilcoxon test showed significance (p=<0.001), meaning that there was an increase in hard skills knowledge, with 87.1% of participants experiencing an increase in individual scores. Conclusion: The education programme proved to be effective in increasing nutritional knowledge, which is an important asset for the prevention of stunting in the community. Health and education agencies continue to conduct regular nutritional counselling for pregnant women.